Tanshinone IIA: A Review of its Anticancer Effects - Fang, Zhong‐ying; Zhang, Miao; Liu, Jia-ning; Zhao, Xue; Zhang, Yong-qing; Fang, Lei (Frontiers in Pharmacology, 2021)
Tanshinone IIA (Tan IIA) is a pharmacologically lipophilic active component isolated from the roots and rhizomes of the Chinese medicinal herb Salvia miltiorrhiza Bunge (Danshen). Tan IIA is currently used in China and other neighboring countries to treat patients with cardiovascular system, diabetes, apoplexy, arthritis, sepsis, and other diseases. Recently, it was reported that tan IIA could have a wide range of antitumor effects on several human tumor cell lines, but its mechanism of tan IIA is relatively scattered in cancer. This review aimed to summarize the recent advances in the anticancer effects of tan IIA and to provides a novel perspective on clinical use of tan IIA.